2014
DOI: 10.1515/hsz-2014-0253
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory caspases: key regulators of inflammation and cell death

Abstract: Abstract:The innate immune system represents the first line of defence against infectious agents, and co-ordinates cellular and molecular mechanisms that result in effective inflammatory and anti-microbial responses against pathogens. Infection and cellular stress trigger assembly of canonical and noncanonical inflammasome complexes that activate the inflammatory caspases-1 and -11, respectively. These inflammatory caspases play key roles in innate immune responses by inducing pyroptosis to halt intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 109 publications
0
55
0
Order By: Relevance
“…Interestingly, they also reported that caspase-12 deficient mice were shown to resistant to septic shock in an experimental mouse model of sepsis, suggesting the critical role of caspase-12 in sepsis condition. Fernandez and Lamkanfi suggested that caspase-12 directly binds to the microbial components and hampers the replication of pathogens by inducing pyroptosis and confers the resistance against sepsis [96]. Moreover, the association of human caspase-12 with susceptibility to sepsis in individuals of African and Indian population has been documented by previously published studies [97, 98].…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, they also reported that caspase-12 deficient mice were shown to resistant to septic shock in an experimental mouse model of sepsis, suggesting the critical role of caspase-12 in sepsis condition. Fernandez and Lamkanfi suggested that caspase-12 directly binds to the microbial components and hampers the replication of pathogens by inducing pyroptosis and confers the resistance against sepsis [96]. Moreover, the association of human caspase-12 with susceptibility to sepsis in individuals of African and Indian population has been documented by previously published studies [97, 98].…”
Section: Introductionmentioning
confidence: 98%
“…Casp1 exists in inactive pro-forms in the cytosol and is activated when cleaved into p10 and p20 catalytic domain fragments [12], which is required for interleukin 1 beta (IL-1β) processing, IL-18 release, and induction of pyroptosis. Casp1 is activated by the canonical Nod-like receptors (NLRs, typically via their caspase recruitment domain [CARD] or Pyrin domain), such as through direct CARD-CARD interactions (e.g., NLRP1b and NLRC4) or apoptosis-associated speck-like protein containing a CARD (ASC, also known as PYCARD)-mediated interactions (e.g., NLRP3, AIM2 and Pyrin) [13]. ASC is only composed of a Pyrin and CARD domain, and is an adapter protein for Casp1 activation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Together with caspase-11 and -12 in mice and caspase-4, -5, and -12 in humans, caspase-1 belongs to the family of inflammatory caspases, which are produced as inactive forms. After the detection of pathogens or cytoplasmic danger signals, inactive caspase-1 monomers recruit to multiprotein complexes referred to as inflammasomes (1)(2)(3). In such inflammasomes, inactive procaspases are autoprocessed into caspase activation and recruitment domains (CARDs), 2 the p10 and the p20 subunits (4).…”
mentioning
confidence: 99%